The Impact of Quality of Destination Attributes on Tourist Satisfaction - The Case of Bhutan (Global Journal of Management and Business Research, 2019)
Abstract not found
Keywords: destination attributes; overall satisfaction; expectations; multiple regressions; bhutan.